The Vietnam War - Daynes, Katie; Tomlins, Karen (Usborne London, 2008)
A new title in Young Reading Series Three, which is aimed at children whose reading ability and confidence allows them to tackle longer and more complex stories. The book tells the story of the Vietnam War, from Vietnam's struggle for independence from the French to the protracted peace process which bought to conflict with the USA to an end. It contains fascinating details about the guerrilla nature in which fighting was conducted, major offensives, the daily life of a soldier and how public opinion in the USA turned against the War. It is illustrated with a combination of photography and comic book style illustrations where appropriate